2021
DOI: 10.1002/art.41619
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 Outcomes in Patients With Systemic Autoimmune Rheumatic Diseases Compared to the General Population: A US Multicenter, Comparative Cohort Study

Abstract: Objective. Patients with systemic autoimmune rheumatic diseases (ARDs) continue to be concerned about risks of severe coronavirus disease 2019 outcomes. This study was undertaken to evaluate the risks of severe outcomes in COVID-19 patients with systemic ARDs compared to COVID-19 patients without systemic ARDs.Methods. Using a large multicenter electronic health record network, we conducted a comparative cohort study of patients with systemic ARDs diagnosed as having COVID-19 (identified by diagnostic code or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
138
2
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 136 publications
(151 citation statements)
references
References 20 publications
(19 reference statements)
7
138
2
4
Order By: Relevance
“…Among these individuals, the risk for incident viral infections (e.g., herpes zoster) was rated as being higher than for the general population (20)(21)(22). There was also agreement that AIIRD patients are likely to be at increased risk for hospitalized SARS-CoV-2 infection (23)(24)(25)(26)(27) and that age, race/ethnicity (especially for underrepresented minorities), and sex were important risk factors that needed to be considered (28)(29)(30)(31) in evaluating risk at the individual patient level. Multimorbidity was felt to likewise play an important role in the risk for developing COVID-19.…”
Section: General Considerations Related To Vaccinationmentioning
confidence: 98%
“…Among these individuals, the risk for incident viral infections (e.g., herpes zoster) was rated as being higher than for the general population (20)(21)(22). There was also agreement that AIIRD patients are likely to be at increased risk for hospitalized SARS-CoV-2 infection (23)(24)(25)(26)(27) and that age, race/ethnicity (especially for underrepresented minorities), and sex were important risk factors that needed to be considered (28)(29)(30)(31) in evaluating risk at the individual patient level. Multimorbidity was felt to likewise play an important role in the risk for developing COVID-19.…”
Section: General Considerations Related To Vaccinationmentioning
confidence: 98%
“…17 A large cohort study conducted in the USA reported a higher rate of venous thromboembolism in patients with AIIRD within 30 days follow-up of COVID-19 infection compared with the matched population without AIIRD. 18 A large US electronic health records based study investigated temporal trends in COVID-19 outcomes in patients with rheumatic diseases over the course of the pandemic. 19 The risks of severe COVID-19 outcomes, including risks of hospitalisation, respiratory failure, mechanical ventilation, renal failure and death after COVID-19 diagnosis, have improved over time in patients with rheumatic but remain substantial.…”
Section: Is Covid-19 Disease More Severe In Patients With Aiird?mentioning
confidence: 99%
“…These data are derived largely from numerous small case-controlled investigations. In general, patients with IMIDs such as rheumatic diseases [49], IBD [50], and multiple sclerosis [42] appear to be more vulnerable to severe outcomes (ie, hospitalization, ICU status, and death), but after adjusting for comorbid conditions that are overrepresented in patients with autoimmune disease, such as cardiovascular disease, this risk is greatly diminished in most [49], but not all investigations. Preliminary data, primarily derived from case reports and small case studies have also associated SARS-CoV-2 infection with disease flares in patients with pre-existing IMIDs, but conclusions of causation should be avoided [51].…”
Section: Critical Questions What Do We Know About the Clinical Course Of Patients With Imids Who Develop Covid-19?mentioning
confidence: 99%